Growth Performance, Apparent Ileal Digestibility, and Nutrient Transporter Gene Expressions of Broilers Fed Seaweed-Supplemented Diets - Azizi, M. N.; Loh, T. C.; Foo, H. L.; Izuddin, W. I. (Tropical Animal Science Journal, 2024)
Seaweed provides macro-, micro-nutrients, and biological bioactive components that may improve broiler production. The study aimed to evaluate the effects of various levels of brown seaweed (BS) and green seaweed (GS) on growth performance, carcass characteristics, apparent ileal digestibility (AID), and hepatic growth and nutrient transporter gene expressions. The study followed a completely randomized design (CRD) (twelve treatments, six replicates, and seven birds per replicate). The dietary treatments contained: basal diet [negative control (NC)], basal diet + vitamin E (100 mg/kg feed) [positive control (PC)], basal diet + 0.25%, 0.50%, 0.75%, 1.0%, and 1.25% BS and GS, respectively. The data were analyzed using the General Linear Model (GLM) of the statistical analysis system (SAS 9.4) by one-way ANOVA. Duncan’s Multiple Range Test was used to assess the significant differences between treatment groups at p